Effect of Modified Growth Method on the Structural and Optical Properties of InAs/GaAs Quantum Dots for Controlling Density - Ryu, Sung-Pil; Cho, Nam-Ki; Lim, Ju-Young; Lee, Hye-Jin; Choi, Won-Jun; Song, Jin-Dong; Lee, Jung-Il; Lee, Yong-Tak (JAPAN SOC APPLIED PHYSICS, 2009)
We introduce a thermal treatment, namely, a growth technique to form low-density quantum dots (QDs) with homogeneous InAs deposition, and study the structural and optical properties of InAs/GaAs QDs during the formation of dots by the thermal treatment. The structural and optical properties are studied by atomic force microscopy and photoluminescence (PL). We achieve a wide range of dot densities from 10(10) to 10(6) per cm(2) by adjusting the thermal treatment temperature. The uniformity of InAs dots improves as the thermal treatment temperature increases. Comparing PL spectra with those in the literature, we confirm that the dots in this work are not QDs but small quasi-three-dimensional (Q3D) clusters. Q3D clusters are left after the thermal treatment. This behavior of Q3D is different from that of the QDs reported in the literature. We conclude that three phenomena occur during the thermal treatment: 1) In segregation, 2) In re-evaporation, and 3) the intermixing of InAs. As a result, we conclude that the thermal treatment is a very useful method for controlling the dot density. (C) 2009 The Japan Society of Applied Physics
Keywords: MOLECULAR-BEAM EPITAXY; INAS; GAAS; SEGREGATION; DEPOSITION; MORPHOLOGY; SYSTEM